Influencing factors that build brand perception towards North Borneo University College / Evy Requel Rahim - Rahim, Evy Requel (2020)
This chapter will start with the background of study, which provided an overview North Borneo University College (NBUC). Some aspects on brand perception specifically towards this private university also had been highlighted. The researcher had observed that the people commonly would do a comparison on several universities; specifically based on individuals’ perception. Therefore, researcher believed that brand perception had become an important aspect where the marketers can use as their mechanism in enhancing their services on educational field. The problem statement addresses the various potential issues which been identified further in the study. This is then followed by the statement of research questions, research objectives, scope of study and the significant of study.